2021
DOI: 10.1155/2021/5478227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritional Ingredients, Biologically Active Materials, and Pharmacological Activities of Stropharia rugosoannulata Grown under the Bamboo Forest and in the Greenhouse

Abstract: Evaluations of the nutritional ingredients, biologically active materials, and pharmacological activities (antibacterial and antioxidant) of two types of Stropharia rugosoannulata, grown under the bamboo forest and in the greenhouse, respectively, were carried out in this study. The nutritional ingredient tests included moisture, ash, crude protein, crude fat, crude fiber, total carbohydrates, total sugar, mineral elements, vitamins, and amino acids. The biologically active material assays included total flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…4 showed the results of the effects of SD, RSD, HD, VFD, and MD on the mineral elements in S. rugosoannulata. It showed that all five kinds of dried samples contained K, Ca, Mg, Na, and P as major elements, and Fe, Zn, Mn, Cu, and Se as trace elements, which was in agreement with previous reports [7,39]. K plays an Notes: results were expressed as means ± SE (n = 3).…”
Section: Proximate Compositionsupporting
confidence: 91%
See 2 more Smart Citations
“…4 showed the results of the effects of SD, RSD, HD, VFD, and MD on the mineral elements in S. rugosoannulata. It showed that all five kinds of dried samples contained K, Ca, Mg, Na, and P as major elements, and Fe, Zn, Mn, Cu, and Se as trace elements, which was in agreement with previous reports [7,39]. K plays an Notes: results were expressed as means ± SE (n = 3).…”
Section: Proximate Compositionsupporting
confidence: 91%
“…Amino Acid Composition. The compositions of amino acids were determined by a reversed-phase HPLC method according to the previous report [7]. Retention data were collected with a Waters ACQUITY chromatographic system (Waters, Milford, MA, USA) including a 2414 evaporative light scattering detector.…”
Section: Appearance and Colourmentioning
confidence: 99%
See 1 more Smart Citation
“…Stropharia rugosoannulata (Strophariaceae), better known as "Chisongrong" in China, is a type of precious edible mushroom recommended by the United Nations Food and Agriculture Organization (FAO) to be cultivated in developing countries [3]. It has been reported that S. rugosoannulata is a good source of protein, fbre, amino acids, mineral elements, polysaccharides, phenols, and various biologically active substances [4] and shows important pharmacological activities such as antitumor, antihyperglycemic, antibacterial, antioxidant, and coronary heart disease preventative efects [5,6]. Terefore, S. rugosoannulata has become one of the top ten mushrooms in the international mushroom market.…”
Section: Introductionmentioning
confidence: 99%
“…Teir multidrug resistance has driven the development of research aimed at identifying new antimicrobial agents through chemical synthesis or isolation from natural products. We have reported that the aqueous and ethanolic extracts of S. rugosoannulata both showed strong antibacterial activity against E. coli, S. aureus, and P. aeruginosa with MIC from 0.0625 to 1 mg/mL [4]. However, the antibacterial activity of S. rugosoannulata essential oil (SEO) has not been studied up to now.…”
Section: Introductionmentioning
confidence: 99%